Colloidal Silicon Quantum Dot‐Based Cavity Light‐Emitting Diodes with Narrowed and Tunable Electroluminescence. Issue 1 (9th November 2022) - Cheong, I Teng; Mock, Josef; Kallergi, Maria; Groß, Elisabeth; Meldrum, Alkiviathes; Rieger, Bernhard; Becherer, Markus; Veinot, Jonathan G. C.
Abstract: Luminescent colloidal silicon quantum dots (SiQDs) are explored as alternatives to metal‐based quantum dots for light‐emitting diodes (LEDs) because of the abundance and biocompatibility of silicon. To date, the broad electroluminescence (EL) bandwidth (>100 nm) and blueshifting of EL at high applied voltages of SiQD‐LEDs are outstanding challenges that limit a competitive spectral purity and device stability. Herein, the fabrication and testing of SiQD‐LEDs that incorporate a Fabry–Pérot cavity are reported which exhibit a narrow spectral linewidth as low as ≈23 nm. The presented devices also provide wavelength and visual stability from +4 to +8 V, as well as spectral tunability. Abstract : Silicon quantum dot light‐emitting diode (SiQD‐LED) incorporated with a Fabry–Pérot cavity is designed and fabricated here. The cavity SiQD‐LEDs exhibit narrow spectral linewidths as low as ≈23 nm (vs >100 nm linewidth of normal SiQD‐LEDs), meanwhile, provide spectral and visual stability from +4 to +8 V as well as spectral tunability.